(3GdeLjO aj EYQGH GdbQBf GdeLjOs - (3CHh ESMGb EHQGgje Hf eMeO GdUaGbSj,J (B742 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TQafG HMaX cJGHg hHYO adeG cGf GdSGf GdYQHi gh GdWQjb GdSfi Edi age eaQOGJ GdbQBf GdYRjR hJQcjHGJg hSejJg HGdeLjO ai EYQGH GdbQBf GdeLjO EYQGH GdHSedI s
(3BNQgG (B:s
(3hbGd CHh GdHbGA WdHhG EQgGHge aGHbi ESJaYd Ydi HGHg ef GdWdH hGdChd CXgQ ef MjK GdeYfi hGddg SHMGfg hJYGdi CYde Je GdLRA GdChd ef EYQGH GdSaGbSi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B82s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1607s
Keywords: (3GdJaSjQ hYdhe GdbQBfs